2014
DOI: 10.1371/journal.pone.0100297
|View full text |Cite
|
Sign up to set email alerts
|

TERT Promoter Mutations Lead to High Transcriptional Activity under Hypoxia and Temozolomide Treatment and Predict Poor Prognosis in Gliomas

Abstract: ObjectiveThis study explored the effects of telomerase reverse transcriptase (TERT) promoter mutations on transcriptional activity of the TERT gene under hypoxic and temozolomide (TMZ) treatment conditions, and investigated the status and prognostic value of these mutations in gliomas.MethodsThe effect of TERT promoter mutations on the transcriptional activity of the TERT gene under hypoxic and TMZ treatment conditions was investigated in glioma cells using the luciferase assay. TERT promoter mutations were de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
48
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(52 citation statements)
references
References 32 publications
3
48
0
1
Order By: Relevance
“…Telomerase reverse transcriptase (TErT), a catalytic subunit of telomerase that includes an rnA component (TErC), therewithal maintains the telomere homeostasis and chromosomal integrity (15). reactivation of TErT has been detected in approximately 90% of human cancers (3,(17)(18)(19)(20). This study attempted to investigate whether immunohistochemical expression of TErT differs in neoplastic and nonneoplastic pituitary tissues and aimed to investigate whether TErT expression is related to clinicopathological features of pituitary adenomas.…”
Section: Comparisons Of Cytoplasmic Tert Expression With Clinicopathomentioning
confidence: 99%
See 1 more Smart Citation
“…Telomerase reverse transcriptase (TErT), a catalytic subunit of telomerase that includes an rnA component (TErC), therewithal maintains the telomere homeostasis and chromosomal integrity (15). reactivation of TErT has been detected in approximately 90% of human cancers (3,(17)(18)(19)(20). This study attempted to investigate whether immunohistochemical expression of TErT differs in neoplastic and nonneoplastic pituitary tissues and aimed to investigate whether TErT expression is related to clinicopathological features of pituitary adenomas.…”
Section: Comparisons Of Cytoplasmic Tert Expression With Clinicopathomentioning
confidence: 99%
“…TErT expression is suppressed in normal adult somatic tissues, but it can be expressed in embryogenic tissues. reactivation of TErT has been detected in approximately 90% of human cancers (3,(17)(18)(19)(20). Thus, TErT activity in pituitary adenomas has been the subject of a few studies that showed contradictory results (3,16,21).…”
Section: Introductionmentioning
confidence: 99%
“…1) [6,11,12,16,[26][27][28][29][30][31][32]. Those 11 studies involved a total of 3,444 patients with gliomas [6,11,12,16,[26][27][28][29][30][31][32]. Table 1 showed the main characteristics of those 11 included studies in the meta-analysis (Table 1).…”
Section: Characteristics Of Studiesmentioning
confidence: 99%
“…Table 1 showed the main characteristics of those 11 included studies in the meta-analysis (Table 1). Five studies focused on the prognostic role of TERT promoter mutations in patients with gliomas [11,12,28,29,32], five studies focused on the prognostic role of TERT promoter mutations in patients with glioblastoma [6,16,26,30,31], and one study focused on the prognostic role of TERT promoter mutations in patients with medulloblastoma [27]. Among those 11 studies, nine studies reported adjusted HRs [6,11,12,16,26,[28][29][30][31].…”
Section: Characteristics Of Studiesmentioning
confidence: 99%
See 1 more Smart Citation